Rove Beetles of the World, Staphylinidae (Insecta: Coleoptera: Staphylinidae) - J. Howard Frank; Michael C. Thomas (EDIS)
This document is EENY-114, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 1999. Revised: March 2002.